Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

Mapping Global Terrestrial Spatiotemporal Dynamics of Atmospheric CO 2 Carbon Isoscapes for Ecological Studies - Hanlin Feng; Xiang Wang; Philippe Ciais; Guo Chen; Xiaoying Gong; David Makowski; Lixin Wang; Zheng Fu (Global Change Biology, 2026)
The isotopic composition of atmospheric carbon dioxide (δ 13 C atm ) provides insights into the terrestrial carbon cycle. However, long‐term global δ 13 C atm maps with both high spatial resolution and continuous temporal coverage remain scarce. Here, we present a new global terrestrial dataset of monthly δ 13 C atm isoscapes from 2001 to 2020 at 0.05° spatial resolution, developed by integrating in situ observations with optimized 4D CO 2 concentration fields from inversion outputs, reanalysis data, and geographic information using machine learning. Among four tested models, the Gradient Boosting Machine demonstrated the highest predictive performance under random validation ( R 2 = 0.80, RMSE = 0.12‰) and maintained robust performance across three spatially independent validation frameworks ( R 2 = 0.56–0.67, RMSE = 0.16‰–0.19‰). Key predictors were air temperature and atmospheric CO 2 concentration. The resulting global terrestrial isoscapes reveal strong spatial and temporal heterogeneity. Model predictions closely align with National Oceanic and Atmospheric Administration (NOAA) marine boundary layer (MBL) observations in terms of trend magnitude, seasonal amplitude ( 13 C atm seasonal amplitude varies from 0.06‰ in Southern Hemisphere mid‐latitudes to 0.6‰ in Northern Hemisphere high latitudes, indicating strong hemispheric asymmetry. Moreover, over 99.8% of global terrestrial grid cells show negative trends in all seasons, with a global terrestrial average annual depletion rate of −0.030‰ ± 0.0006‰ year −1 . The trend shows stronger depletion during summer and autumn, reaching its peak in August (−0.035‰ ± 0.0012‰ year −1 ), while spring and winter seasons remain comparatively stable. This study delivers a long‐term, high‐resolution global terrestrial δ 13 C atm isoscape dataset, offering a valuable tracer for carbon cycle research and, importantly, robust data support for large‐scale investigations of carbon–water coupling in terrestrial ecosystems.

Fish community and its relationships with environmental factors in the Jiupan River, a secondary tributary of the Three Gorges Reservoir - Junquan Ren; Zhenxin Chen; Kaiyang Wu; Lilong Chen; Rongchao He; Mengqiao Long; Yankun Shen; Hanlin Wang; Mei Fu; Hongjian Lv; Weizhi Yao (Environmental Biology of Fishes, 2026)

Engineering charge transfer via built-in electric field in Z-scheme heterojunction photocatalysts for antibiotic degradation in wastewater - Hanlin Wei; Kaiyi Chen; He Wang; Xin Wang; Lianshe Fu; Wei Dai; Tinghai Yang (Environmental Research, 2026)

Impacts of the mega cascade reservoirs on riverine hydrothermal regimes based on deep learning - Meixiu Yu; Jinjie Guan; Jianyun Zhang; Junliang Jin; Qingshe Meng; Hanlin Song; Zixuan Xu; Xiaolong Liu; Jiayi He; Ting Fu (Journal of Hydrology, 2026)

Polystyrene nanoplastics induce ovarian injury by PI3K-Akt pathway-driven macrophage extracellular trap formation - Yingying Chen; Linli Yang; Yuanyuan Li; Lulu Si; Hanlin Fu; Tianjiao Lai; Ruixia Guo (Environmental Pollution, 2025)

Efficient ammonia production from air via synergistic plasma–photoelectrochemical over Cu2O/Cu/CeO2 type-II heterojunction - Kaiyi Chen; Hanlin Wei; He Wang; Lianshe Fu; Rute A.S. Ferreira; Tinghai Yang (Chemical Engineering Journal, 2025)

Self-powered drifting buoy for maritime anomaly traffic monitoring via electromagnetic-triboelectric coupling - Hanlin Zhou; Zhiqiang Yang; Zhi Cao; Junbo Wang; Hao Qian; Jizhong Deng; Yuxuan Zhou; Yingwei Zhao; Hailin Fu; Zhiyi Wu (Chemical Engineering Journal, 2025)

Higher warming rate in global arid regions driven by decreased ecosystem latent heat under rising vapor pressure deficit from 1981 to 2022 - Jingping Wang; Hanlin Niu; Shupeng Zhang; Xiuzhi Chen; Xiaosheng Xia; Yanwu Zhang; Xingjie Lu; Bin He; Tongwen Wu; Chaoqing Song; Zheng Fu; Jingyu Yao; et al. (Agricultural and Forest Meteorology, 2025)

The integration of machine learning into proteomics advances food authentication and adulteration control - Hongfei Li; Hanlin Mo; Yu-Chen Song; Guanying Chen; Cai-E Wu; Fu-Yuan Zhu (Trends in Food Science & Technology, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Reduction of CO2 to C2 products by tandem actives sites of a novel 2D/3D structured photoelectrocatalyst Ag/Cu2O/g-C3N4 - Hanlin Qi; Xiaoyu Han; Jiangpeng Fu; Jiayang Ma; Xuan Jia; Meichao Zhao; Xiaona Wang; Zhongtian Fu; Jun Zhang; Xin Zhao (Journal of Environmental Chemical Engineering, 2025)

The BCM1-EGY1 module balances chlorophyll biosynthesis and breakdown to confer chlorophyll homeostasis in land plants - Dali Fu; Hanlin Zhou; Bernhard Grimm; Peng Wang (Molecular Plant, 2025)

Hepatocellular carcinoma epi-immunotherapy with polyion complex micelles co-delivering HDAC8 inhibitor and PD-L1 siRNA - Jinhua Zhao; Taiqing Liu; Yinqi Li; Xiaodong Yang; Xiaoyu Wang; Yunhai Fu; Yeteng Zheng; Ziying Yao; Jingwen Wang; Hanlin Gong; Zhiyao He (Chemical Engineering Journal, 2025)

A novel ternary AgBr/Ag3PO4/h-BN photocatalyst material for tetracycline degradation: Enhancement mechanism, degradation pathway and product toxicity evaluation - Xuan Jia; Xiaoyu Han; Jiangpeng Fu; Hanlin Qi; Junyan Liu; Tianfang Han; Zhongtian Fu; Binbin Wei; Xin Zhao; Feng Guo (Journal of Environmental Chemical Engineering, 2024)

Weathering-induced organic matter enrichment in marine-continental transitional shale: A case study on the early Permian Taiyuan Formation in the Ordos Basin, China - Zhengfu Zhao; Caineng Zou; Shifeng Dai; Zhaojie Guo; Yong Li; Arne Thorshøj Nielsen; Niels Hemmingsen Schovsbo; Zhenhua Jing; Hanlin Liu; Ming Yuan; Fangliang Fu; Jia Yin; et al. (International Journal of Coal Geology, 2024)

Science- and Risk-Based Stability Strategies to Support Product Lifecycle Changes - Lori McCaig; Steven Nowak; Alexander Abbott; Jenny Carhart; Megan E. McMahon; Elke Debie; Hanlin Li; Francis Maina; Andrea J. Ji; Mingkun Fu; Yan Wu; Andrew Lennard; et al. (The AAPS Journal, 2024)

An Adversarial Single-Domain Generalization Network for Fault Diagnosis of Wind Turbine Gearboxes - Xinran Wang; Chenyong Wang; Hanlin Liu; Cunyou Zhang; Zhenqiang Fu; Lin Ding; Chenzhao Bai; Hongpeng Zhang; Yi Wei (Journal of Marine Science and Engineering, 2023)
In deep learning-based fault diagnosis of the wind turbine gearbox, a commonly faced challenge is the domain shift caused by differing operational conditions. Traditional domain adaptation methods aim to learn transferable features from the source domain and apply them to the target data. However, such methods still require access to target domain data during the training process, which limits their applicability in real-time fault diagnosis. To address this issue, we introduce an adversarial single-domain generalization network (ASDGN). It relies solely on data from a single length of data acquisition in wind turbine fault diagnosis. This novel approach introduces a more flexible and efficient solution to the field of real-time fault diagnosis for wind turbines.

An enhanced tilted-angle acoustic tweezer for mechanical phenotyping of cancer cells - Hanlin Wang; Joe Boardman; Xiaoyan Zhang; Chao Sun; Meng Cai; Jun Wei; Zhiqiang Dong; Mingqian Feng; Dongfang Liang; Sheng Hu; Yu Qian; Shuang Dong; et al. (Analytica Chimica Acta, 2023)

Correction to: Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

A survey of municipal solid waste landfills in Beijing during 2009–2011 - Xinyi Liu; Huizhen Fu; Hanlin Jiang; Yan Shao; Xiaoyang Wu; Zhenshan Li (Environmental Science and Pollution Research, 2019)

Middle triassic post-orogenic extension on Hainan Island: Chronology and geochemistry constraints of bimodal intrusive rocks - LiMei Tang; HanLin Chen; ChuanWan Dong; ShuFeng Yang; ZhongYue Shen; XiaoGan Cheng; LuLu Fu (Science China Earth Sciences, 2013)